2023
DOI: 10.3390/pharmaceutics15051374
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Fluorescent Hydroxyapatite Nanoparticles for Targeted Photothermal Cancer Therapy

Abstract: Near-infrared (NIR) fluorophores have attracted great attention due to their excellent optical and photothermal properties. Among them, a bone-targeted NIR fluorophore (named P800SO3) contains two phosphonate groups, which play important roles in binding with hydroxyapatite (HAP) as the main mineral component of bones. In this study, biocompatible and NIR fluorescent HAP nanoparticles functionalized with P800SO3 and polyethylene glycol (PEG) were readily prepared for tumor-targeted imaging and photothermal the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It is a major component of the bones and teeth in vertebrates 1,2 . HAP has the advantages of high biocompatibility, biostability, bioactivity, and stability, making it widely applied in the field of bioceramics 3–6 . Furthermore, HAP has been utilized in various applications, including bone grafting, drug/gene delivery, protein adsorption, hydroxyapatite coatings, and catalytic supports 7–12 .…”
Section: Figurementioning
confidence: 99%
“…It is a major component of the bones and teeth in vertebrates 1,2 . HAP has the advantages of high biocompatibility, biostability, bioactivity, and stability, making it widely applied in the field of bioceramics 3–6 . Furthermore, HAP has been utilized in various applications, including bone grafting, drug/gene delivery, protein adsorption, hydroxyapatite coatings, and catalytic supports 7–12 .…”
Section: Figurementioning
confidence: 99%
“…HAp theranostic agents can be applied to the oncology field. HAp nanoparticles can be engineered to deliver chemotherapy drugs or gene therapies to tumour cells while being visualised using imaging modalities for accurate tumour targeting and therapy monitoring [50] . HAp theranostics can also be used in tissue engineering and regenerative medicine applications [51] .…”
Section: Hydroxyapatite For Theranosticsmentioning
confidence: 99%
“…Among all the phototherapy methodologies, photothermal therapy (PTT), which adopts photothermal agents (PTAs) to convert absorbed photons into hyperthermia, is an attractive tumor treatment modality [ 12 , 13 , 14 , 15 , 16 ]. Numerous studies have demonstrated that photothermal therapy exhibits remarkable efficacy in cancer treatment [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%